2021
DOI: 10.1111/exd.14443
|View full text |Cite
|
Sign up to set email alerts
|

Protein tyrosine phosphatase 1B regulates fibroblasts proliferation, motility and extracellular matrix synthesis via the MAPK/ERK signalling pathway in keloid

Abstract: Keloids clinically present as firm, rubbery nodules that result from abnormal wound healing in response to skin trauma or inflammation. It is characterized by excessive proliferation of fibroblasts, increased deposition of extracellular matrix (ECM), invasive growth beyond the original wound bounders and infiltration to normal tissue. Keloids can cause functional and cosmetic deformities which significantly affects the life quality of patients and brings physical and psychological damage to them. 1 Additionall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 36 publications
1
1
0
Order By: Relevance
“…Regarding molecular functions, these genes were mainly enriched in chemokine receptor binding, growth factor receptor binding, integrin binding, etc., which was consistent with previous studies [ 53 55 ]. KEGG analysis showed that 44 keloid-related immune genes were mainly enriched in the Jak-STAT signaling pathway, MAPK signaling pathway, TGF-β signaling pathway, and other related signaling pathways, consistent with previous studies [ 56 58 ]. These results suggest that 44 keloid-related immune genes may regulate these key signaling pathways during the development and progression of keloids, which needs to be further investigated.…”
Section: Discussionsupporting
confidence: 90%
“…Regarding molecular functions, these genes were mainly enriched in chemokine receptor binding, growth factor receptor binding, integrin binding, etc., which was consistent with previous studies [ 53 55 ]. KEGG analysis showed that 44 keloid-related immune genes were mainly enriched in the Jak-STAT signaling pathway, MAPK signaling pathway, TGF-β signaling pathway, and other related signaling pathways, consistent with previous studies [ 56 58 ]. These results suggest that 44 keloid-related immune genes may regulate these key signaling pathways during the development and progression of keloids, which needs to be further investigated.…”
Section: Discussionsupporting
confidence: 90%
“…Previous reports indicated that TIMP-1 suppression maybe associated with increased fbrillar collagen deposition and extensively fragmented elastic lamellae accumulation; in addition, TIMP-1 defciency was also correlated to increased tissue infammation evoking the importance of TIMP-1 in restricting extracellular matrix degradation and abnormal tissue scarring under pathological conditions [55]. PTP1B overexpression and/or overactivation has been previously reported to critically afect and downregulate the expression of both TIMP-1 and TIMP-2 in liver tissue and HSC [56,57], which correlate with our observed data, in which EMS-afected livers displayed suppressed TIMP-1 gene expression.…”
Section: Discussionmentioning
confidence: 96%
“…PTP1B is encoded by the protein tyrosine phosphatase non-receptor type 1 gene, which creates a 435 amino acid protein with a hydrophobic C-terminal sequence that targets PTP1B to the ER [31]. PTP1B was conventionally considered a routine treatment for diabetes [32] and obesity originally [33].…”
Section: Discussionmentioning
confidence: 99%